Food choice factors affecting green food attitude in Klang Valley - Lidew, Lidiana; Md Jusoh, Zuroni; Sulaiman, Norhasmah; Abdul Rahim @ Abdul Wahab, Husniyah; Abu Bakar, Elistina; Jamaluddin, Askiah (Malaysian Consumer and Family Economics Association, 2015)
The purpose of this study is to determine food choice factors that influence consumers’ attitude towards green food based on the Food Choice Questionnaire (FCQ) developed by Steptoe, Pollard & Wardle (1995). Data were collected by interviewing a total number of 400 respondents chosen by using simple random sampling method from four areas in Klang Valley. Pearson correlation and multiple linear regressions were used to analyze the information of a factor that affect consumers’ attitude. FCQ is used in this study to determine the food choice factors that influence consumer’s attitude. The results indicated that most of the factors in FCQ: sensory appeal (r=0.115 p<0.022), natural content (r=0.202, p<0.000), health (r=0.257, p<0.000), ethical concern (r=0.169, p<0.001), body weight control (r=0.167, p<0.001) convenience (r=0.185, p<0.000), mood (r=0.186, p<0.000), and price (r=0.168, p<0.001) have a significant positive relationship with green food attitude except familiarity. Multiple linear regression analysis found that health is the most significant factors more likely to affect consumers’ attitude towards green food with the value of 0.009. It can be concluded that health contributes in encouraging consumers to consume green food; and by referring to this relationship, it can also be presumed that green food consumption might improve consumer health well-being, including a positive change in their consumption. Future research should focus on a similar study with an extended scope to all states in Malaysia. Appropriate effective strategies on implementing health promotion must be done as well as in promoting green food.